Marital rape or conjugal debit? Frameworks of domestic violence in the soap opera O Outro Lado do Paraíso - Peixoto, Danielle Silva (2022)
The objective of this article is to analyze which frameworks can be apprehended in the soap opera O Outro Lado do Paraíso from the representation of the sexual violence scene.  The analysis of the interactive situation is the methodology used to apprehend these framings. The findings reveal that the elements proposed for the construction of the representation of the nuptial scene trigger primary frameworks of our culture that configure, within the soap opera, the situation of sexual violence, known as marital rape.